The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s00059-009-3313-7
|View full text |Cite
|
Sign up to set email alerts
|

Wertigkeit des Biomarkers BNP bei HIV-infizierten Patienten

Abstract: The data demonstrate that BNP is suitable for the detection of cardiac disorders in HIV-infected subjects. Therefore, BNP could be an appropriate tool for a screening program for HIV-associated disorders in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In addition to being a marker of cardiac dysfunction, increased circulating levels of NT-proBNP are predictors of coronary heart disease and stroke in the general population [39]. The association of increased levels of pro-BNP with cardiovascular events occurrence in PLWH had only been shown in the SMART trial and the HIV-HEART study, in both cases with baseline pro-BNP levels [40, 41]. Availability of biomarkers levels during follow-up allowed assessing their predictive role also in patients receiving ART, and at a nearest time to event development.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being a marker of cardiac dysfunction, increased circulating levels of NT-proBNP are predictors of coronary heart disease and stroke in the general population [39]. The association of increased levels of pro-BNP with cardiovascular events occurrence in PLWH had only been shown in the SMART trial and the HIV-HEART study, in both cases with baseline pro-BNP levels [40, 41]. Availability of biomarkers levels during follow-up allowed assessing their predictive role also in patients receiving ART, and at a nearest time to event development.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in HIV-infected populations have shown elevated BNP associated with increased rates of heart failure, cardiomyopathy, coronary artery disease, pulmonary hypertension, and left and right heart abnormalities measured by echocardiogram and magnetic resonance imaging. [ 24 , 25 , 27 , 37 ] A prior publication in a smaller subgroup from the WIHS cohort found HIV-infected participants had higher NT-proBNP levels, and NT-proBNP was associated with typical risk factors for cardiac and pulmonary disease such as age, race, body mass index, smoking, illicit drug use, hepatitis C infection, hemoglobin, and hypertension. [ 28 ] NT-proBNP may also be produced and secreted in response to mechanisms related to other common phenomenon in the HIV population such as increased inflammatory cytokines important in the pathogenesis of cardiomyopathy—interleukin-1, interleukin-6, and tumor necrosis factor-α,[ 38 , 39 ] exposure to toxins such as cocaine which has cardio-toxic effects,[ 40 , 41 ] and lipotoxicity which can lead to metabolic and cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying cause of the relationship between mortality in HIV infection and elevated NT-proBNP is unclear. Several studies in HIV have shown elevated BNP is associated with cardiac dysfunction,[ 24 , 25 , 37 ] and because inflammation, cocaine use, and metabolic disease can be other mechanisms leading to increased NT-proBNP and are common in HIV-infected persons, NT-proBNP may be a surrogate risk marker of ongoing cardiac damage from chronic inflammation, illicit drug use, or metabolic disease in the HIV-population. [ 38 43 ] We assessed the cause of death in relationship to elevated NT-proBNP level to see if the association was related to cardiac disease specifically, but very few causes of death were clinically attributed to cardiac cause in the early and late HAART periods.…”
Section: Discussionmentioning
confidence: 99%
“…When analyzing 802 HIV-infected patients in their original contribution for cardiac involvement or effects of antiretroviral therapy, Neumann et al [8] found out that patients with a BNP concentration of > 50 pg/ml had a significantly higher rate of heart failure, cardiomyopathy and CAD than the rest. They therefore advocate that BNP should be included in the regular HIV screening program.…”
Section: Biomarker and No End To It?mentioning
confidence: 99%